The Bad Guys - Blabey, Aaron (New York : Scholastic Inc., 2017)
The Bad Guys, Mr. Wolf, Mr. Shark, Mr. Snake, and Mr. Piranha, want to be heroes, and they decide that the way to do it is free the 200 dogs in the city dog pound--but their plan soon goes awry.
School Library Journal, November 2016.
Kirkus Starred, October 2016.
Bulletin (Center for Children's books), December 2016.
2.8
3-6
530L
Keywords: Animals -- Comic books, strips, etc. -- Fiction; Rescue work -- Comic books, strips, etc. -- Fiction; Heroes -- Comic books, strips, etc. -- Fiction; Animals -- Juvenile fiction; Rescues -- Juvenile fiction; Heroes -- Juvenile fiction; Humorous stories; Humorous comics; Graphic novels; Graphic novels